A Mimetic Perspective on Trust (Living in an age of mistrust, 2017)
This chapter discusses the measure of the relevance of mimetic theory for thinking about trust in the context of the events in Baltimore. Mimetic theory prompts to reconceptualize the relation between our disciplines, perhaps it can also help us see that when it comes to an interdisciplinary topic such as trust, what people need before they can "rebuild trust" is to fundamentally rethink it. Perhaps the greatest challenge to introducing the theory is none of the things just mentioned, however, but something paradoxically simpler: mimetic theory begins with the seemingly banal insight that human desire is imitative. Mimetic theory holds that human beings inevitably engage in mimetic rivalry to the point of violence, that indeed this is precisely what violence is. A society in a state of widespread mimetic conflict identifies through accusation one or more certain members, usually marked as marginally different who are deemed to be the "cause" of the spreading violence.